PENGEMBANGAN EKONOMI UMAT - Neli Neli (Cross-border, 2019)
The economic development of the Ummah is a big problem faced by the Ummah today, and in fact the solution can only be done by the Muslims themselves by returning to Allah's rules, including by: instilling entrepreneurial traits for each individual ummah, building strong partnerships/networks. with various parties, especially with fellow Muslims, making policies that are more in favor of the economic growth of the people, by supporting morally and materially sourced from zakat funds, carrying out transactions and economic behavior in accordance with the rules in Islamic teachings.